2013
DOI: 10.1021/bi4003315
|View full text |Cite
|
Sign up to set email alerts
|

Multistep, Eight-Electron Oxidation Catalyzed by the Cofactorless Oxidase, PqqC: Identification of Chemical Intermediates and Their Dependence on Molecular Oxygen

Abstract: The final step of the biosynthesis of the prokaryotic cofactor, PQQ, is catalyzed by PqqC, a cofactorless oxidase that brings about a ring closure and overall eight-electron oxidation of its substrate. Time-dependent acid quenching and subsequent HPLC separation and mass spectrometric analyses of reaction mixtures were performed in order to correlate the structures of intermediates with previously observed UV/Vis signatures. The reaction is composed of four stepwise oxidations: three steps use O2 as the two-el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…1A) was identified more than 25 years ago (4,30), and more recent bioinformatics studies demonstrated a conservation of gene order that includes an occasional gene fusion between PqqD with either the C terminus of PqqC or the N terminus of PqqE (2). However, the description of function for each gene product from this operon has lagged considerably, with PqqC representing the only enzyme within the pathway successfully characterized with regard to structural, spectroscopic, and kinetic properties (5,6,31). Although PqqE had been shown to be a radical SAM enzyme (22), it had not been possible to demonstrate a reaction between the peptide substrate PqqA and PqqE, suggesting either that PqqA must be modified before it can interact with PqqE or that key components of the PqqE system were missing (7).…”
Section: Discussionmentioning
confidence: 99%
“…1A) was identified more than 25 years ago (4,30), and more recent bioinformatics studies demonstrated a conservation of gene order that includes an occasional gene fusion between PqqD with either the C terminus of PqqC or the N terminus of PqqE (2). However, the description of function for each gene product from this operon has lagged considerably, with PqqC representing the only enzyme within the pathway successfully characterized with regard to structural, spectroscopic, and kinetic properties (5,6,31). Although PqqE had been shown to be a radical SAM enzyme (22), it had not been possible to demonstrate a reaction between the peptide substrate PqqA and PqqE, suggesting either that PqqA must be modified before it can interact with PqqE or that key components of the PqqE system were missing (7).…”
Section: Discussionmentioning
confidence: 99%
“…32,33) In all cases, pqqA encodes a small polypeptide, typically 20-30 amino acids in length, containing a conserved glutamate and tyrosine that serve as the backbone in PQQ biogenesis. 34,35) The glutamate and tyrosine undergo post-translational modifications to form the intermediate 3a-(2-amino-2-carboxyethyl)-4,5-dioxo-4,5,6,7,8,9-hexahydroquinoline-7,9-dicarboxylic acid (AHQQ). 32,34) PqqC is the most characterized and has been shown to catalyze the eight-electron oxidation and ring cyclization of AHQQ to form PQQ.…”
Section: Natural Source Of Pqqmentioning
confidence: 99%
“…34,35) The glutamate and tyrosine undergo post-translational modifications to form the intermediate 3a-(2-amino-2-carboxyethyl)-4,5-dioxo-4,5,6,7,8,9-hexahydroquinoline-7,9-dicarboxylic acid (AHQQ). 32,34) PqqC is the most characterized and has been shown to catalyze the eight-electron oxidation and ring cyclization of AHQQ to form PQQ. 35) A large number of bacteria extracellularly excrete PQQ and is indicated as micrograms per mL of broth culture.…”
Section: Natural Source Of Pqqmentioning
confidence: 99%
“…50 Moreover, a progressive closure from an observed open to a closed conformation plays a primordial role in the catalysis (Figure 6). 53 Second, PqqD, a small 10-kDa protein with no homology to any characterized protein, has an indispensable role in the biosynthesis of PQQ that is not yet elucidated. Third, a strictly anaerobic PqqE must function with an O 2 -dependent PqqC and likely, an O 2 -dependent non-heme iron oxygenase (PqqB).…”
Section: Pqq (Pyrroloquinoline Quinone)mentioning
confidence: 99%